Evaluation of use of design templates in the software development - Максим Олександрович Бичок; Ольга Костянтинівна Погудіна (Radìoelektronnì ì komp'ûternì sistemi (Online), 2021)
The subject of study in the article is software development processes using design patterns. The aim is to improve the quality of modern software development projects through the use of experience and knowledge, to build software subsystems that are focused on infrastructure and work with an external client. Objectives: to review the methodology, programming paradigms and the possibility of their application at the design and coding stages of the software development life cycle; development of the concept of using design patterns in software design as knowledge available for reuse, propose an approach to the practical implementation of design patterns to node.js projects. The models used are the Composite design pattern, the Chain of responsibility design pattern. The used methodologies are object-oriented programming, as the most common programming paradigm, a unified modeling language UML for displaying the structure of design patterns. The following results are obtained. Modern methodologies and design paradigms are considered, a classification is formed in the form of a tree structure with a division into declarative and imperative subspecies, it is concluded that within the framework of the study we will use an object-oriented methodology as the most common design paradigm. An example of building an information system of the node.js project is considered. Analyzed the main errors that arise when developing and writing code for working with an external client. The elements of the node.js project and the concepts of structuring their relationship with existing design patterns are considered. An example of a practical implementation of a node.js project and its relationship with the Composite and Chain of responsibility design patterns is considered. In this connection, the work provides the structure of these templates. Findings. The scientific novelty of the results obtained is as follows: the model of design patterns was further developed through their use in the concept of building a node.js application, which makes it possible to improve the quality of interaction between the project team and reduce its execution time.